NOBLE GASES IN LAKES AND GROUND WATERS - Kipfer R.; Aeschbach-Hertig W.; Peeters F.; Stute M. (My University, 2002)
In contrast to most other fields of noble gas geochemistry that mostly regard atmospheric noble gases as 'contamination,' air-derived noble gases make up the far largest and hence most important contribution to the noble gas abundance in meteoric waters, such as lakes and ground waters. Atmospheric noble gases enter the meteoric water cycle by gas partitioning during air / water exchange with the atmosphere. In lakes and oceans noble gases are exchanged with the free atmosphere at the surface of the open water body. In ground waters gases partition between the water phase and the soil air of the quasi-saturated zone, the transition between the unsaturated and the saturated zone. Extensive measurements have shown that noble gas concentrations of open waters agree well with the noble gas solubility equilibrium according to (free) air /(free) water partitioning, whereby the aquatic concentration is directly proportional to the respective atmospheric noble gas abundance (Henry law, Aeschbach-Hertig et al. 1999b). In applications in lakes and ground waters the gas specific Henry coefficient can simplifying be assumed to depend only on temperature and salinity of the water. Hence the equilibrium concentrations of noble gases implicitly convey information on the physical properties of the water during gas exchange at the air / water interface, i.e., air pressure, temperature and salinity of the exchanging water mass. The ubiquitous presence of atmospheric noble gases in the meteoric water cycle defines a natural baseline, which masks other noble gas components until their abundance is sufficiently large that these components can be separated against the natural atmospheric background. For most classical geochemical aspects this typical feature of natural waters may look at first sight as a disadvantage. In fact it turns out to be advantageous because in most cases the noble gas abundance in water can be understood as a binary mixture of two distinct noble gas components - a well- constrained atmospheric component and a residual component of non-atmospheric origin. Only very few processes are able to fractionate atmospheric noble gases. All these processes are controlled by well-understood physical mechanisms, which in consequence constrain air-derived noble gases and any other component completely. In addition to atmospheric noble gases basically two non-atmospheric noble gas components are present in most natural waters: radiogenic noble gases and terrigenic noble gases from different geochemical compartments of the Earth.